Blood in the water : the Attica prison uprising of 1971 and its legacy - Thompson, Heather Ann, 1963- (New York : Pantheon Books, 2016)
"Historian Heather Ann Thompson offers the first definitive telling of the Attica prison uprising, the state's violent response, and the victims' decades-long quest for justice--in time for the forty-fifth anniversary of the events"--
Introduction: State secrets -- The tinderbox: Frank "Big Black" Smith -- Power and politics unleashed: Michael Smith -- The sound before the fury: Tom Wicker -- Retribution and reprisals unimagined: Tony Strollo -- Reckonings and reactions: Robert Douglass -- Inquiries and diversions: Anthony Simonetti -- Justice on trial: Ernest Goodman -- Blowing the whistle: Malcolm Bell -- David and Goliath: Elizabeth Fink -- A final fight: Deanne Quinn Miller.
Includes bibliographical references (pages 579-684) and index.
Bancroft Prize in American History and Diplomacy, 2017
Finalist, National Book Award for Nonfiction, 2016
Keywords: Attica Prison; Prison riots -- New York (State); SOCIAL SCIENCE -- Penology; HISTORY -- United States -- State & Local -- Middle Atlantic (DC, DE, MD, NJ; Criminal law